Formation of Ketoprofen-Malonic Acid Cocrystal by Solvent Evaporation Method - Yudi Wicaksono; Dwi Setyawan; Siswandono Siswandono (Indonesian Journal of Chemistry, 2017)
The purpose of this work was to explore the formation of ketoprofen-malonic acid cocrystal by solvent evaporation method. Early detection of cocrystal formation was conducted by hot stage microscopy and solid-liquid phase diagram. Cocrystal were prepared by solvent evaporation method by using isopropyl alcohol as solvent. Characterization of cocrystal was done by Powder X-Ray Diffractometry (PXRD), Differential Scanning Calorimetry (DSC), Fourier Transform Infrared (FTIR) Spectroscopy and Scanning Electron Microscopy (SEM). The results of hot stage microscopic and solid-liquid phase diagram indicated formation of ketoprofen-malonic acid cocrystal. PXRD and DSC measurements showed stoichiometric ratio of cocrystal ketoprofen-malonic acid (2:1). The ketoprofen-malonic acid cocrystal had melting point at 86.2 °C and unique peaks of PXRD pattern at 2θ of 6.1°, 17.8°, 23.2° and 28.6°. FTIR spectra indicated the formation of cocrystal due to interaction of C=O ketone group of ketoprofen with MA molecule. SEM images show that ketoprofen-malonic acid cocrystal have multi-shaped particles with rough surfaces.